INCREASE SKILLS IN YOUTH CADRE COMMUNICATION THROUGH TRAINING COMMUNICATION EFFECTIVE IN RIDOGALIH VILLAGE - Elizabeth, Beatrix; Giyaningtyas, Ika Juita; Sartika, Aprilina (Abdi Dosen : Jurnal Pengabdian Pada Masyarakat, 2024)
Cadres have a role in preventing disease and improving people's ability to help themselves to achieve optimal health. The incidence of diabetes in adolescents is increasing day by day, so it needs early prevention. Ridogalih Village has Youth cadres but they still can not communicate with the community or their peers. The cadres in Ridogalih village have so far only focused on pregnant women and the elderly, so adolescents do not get good health information. The purpose of community service activities through training adolescent cadres conducted by Medika Suherman University is to improve the knowledge and skills of adolescent cadres so that they can optimize health in Ridogalih village. The method of service carried out provides training on how to communicate effectively, especially with peers. Youth cadres who participated in this training were 30 children who had been appointed as youth cadres before. Evaluation of this activity uses a knowledge questionnaire and a pre-posttest knowledge checklist. The results of the training obtained increased knowledge and skills in effective communication. The results of the training obtained increased knowledge and skills about effective communication. Pre-test cadre knowledge was less as much as 17 or 56.7%, sufficient cadre knowledge as much as 12 or 40.0% and good cadre knowledge as much as 1 or 3.3% while the total score of post test answers in the less category was 4 or 13.3%, enough as much as 16 or 53.3% and good as much as 10 or 33.3%.